THE CONTRIBUTION OF THE BLŪMĪTIS FAMILY TO LATVIA - Gaitniece, Lāsma; Zigmunde, Alīda (Via Latgalica, 2017)
The aim of this article is to show through research in the archives and libraries of Latvia what the Blūmītis family accomplished in the first half of the 20th century for Latvia and how they worked successfully for the children's asylum and the private school. As even today people are speaking about the Blūmītis family, it is necessary to ask the question why this is so and what was so outstanding about this family. Out of the three brothers Osvalds Blūmītis (1903–1971) is the best known. After his studies in England at the Spurgeon's college he returned to his home-village Tilža in Latgale and founded a children's asylum there in 1928. Not only orphans found their new home there, but also many children from poor families who were impoverished by alcoholism. The children belonged to different religious communities; there were not only Baptists like Osvalds Blūmītis, but also Roman-Catholics, Lutheran-Protestants and Russian-Orthodox. Since 1927 a Baptist private school existed in Tilža which later was renamed Osvalds Blūmītis School. Besides this school there existed a children's asylum and a private primary school, which were financed by donations from Latvia, England, Sweden and Brazil. Untill 1940 there was only one institution of this kind for orphans in Latgale. About 200 children found loving care and shelter in it.Osvald’s brothers, Arturs and Adolfs were also Baptist priests as he was. Arturs Blūmītis founded a children's asylum in Jaunjelgava in 1939. In 1940 the Baptist orphan asylums and primary schools were closed. Osvalds Blūmītis left Latvia in 1939 and continued his activities in the US. When he arrived in the US, he started to work as a real estate agent but later continued his work for the Baptist church. Osvalds Blūmītis has helped about 250 Latvians to start a new life after arrival in the US. He fought communism and the policies of the Soviet Union. He also conducted radio shows ''The voice of the oppressed people''. Osvalds, Arturs and Adolfs left the country at the end of the war and became entrepreneurs in America. The active participation of the Blūmītis family – their sister and mother worked in the orphanage too – shows us how much this family was able to do for the needy.